From Camp Town to International City: Us Military Base Expansion and Local Development in Pyeongtaek, South Korea. (8th November 2018) - Martin, Bridget
Abstract: In Pyeongtaek, South Korea, the US military is currently completing construction of its largest overseas base, and tens of thousands of American troops, civilian workers and accompanying family members are relocating to the city. Activist and civil society groups fiercely opposed base expansion in Pyeongtaek, leading to violent confrontations with police in 2006. As many scholars have pointed out, the country's 1980s democratization and 1990s decentralization created the conditions in which such vocal anti‐US and anti‐base politics became possible. Yet it was under the very same conditions that South Korea's central government harnessed local aspirations for urban growth to counter the anti‐base protests. By deregulating land use in Pyeongtaek and promising support for a number of major urban projects, the central government sought to build support for US expansion in the city and re‐cast militarization as a desirable form of 'international city' development. Haunted by the specter of gritty soldier‐entertainment 'camp town' areas and eager to see urban growth, the city government joined with the central government in constructing Pyeongtaek's new urban vision. However, new projects intended as a form of collective compensation displaced thousands and sparked new protest movements.